OCCURRENCE AND CAUSE OF PARASITIC INFECTIONS LEADING TO POPULATION DECLINE OF CHANNA PUNCTATUS (BLOCH) IN NATURAL HABITAT - Jha, Anirudha; GANGOPADHYAY, Krishna; Ray, Rupendu; Homechaudhuri, Sumit (Journal of the Inland Fisheries Society of India, 2016)
OCCURRENCE AND CAUSE OF PARASITIC INFECTIONS LEADING TO POPULATION DECLINE OF CHANNA PUNCTATUS (BLOCH) IN NATURAL HABITAT